Inhibition of Autophagy Maintains ESC Pluripotency and Inhibits Primordial Germ Cell Formation in Chickens - Ying Ding; Juanjuan Zhao; Xianshuai Xu; Qisheng Zuo; Yani Zhang; Kai Jin; Wei Han; Bichun Li (Stem Cells International)
Autophagy plays an important role in the pluripotency and differentiation of stem cells. Transcriptome data showed that the autophagy genes MAP1LC3A and MAP1LC3B were significantly upregulated in primordial germ cells (PGCs). The Kyoto Encyclopedia of Genes and Genome (KEGG) results showed that the lysosome signaling pathway, which is related to autophagy, was significantly enriched in PGCs. Quantitative RT-PCR, western blotting, and transmission electron microscopy (TEM) results showed that autophagy was expressed in both embryonic stem cells (ESCs) and PGCs but was significantly activated in PGCs. To explore the role of autophagy in the differentiation of chicken ESCs into PGCs, autophagy was activated and inhibited using rapamycin and bafilomycin A1, respectively. Results of qRT-PCR, flow cytometry, and indirect immunofluorescence showed that the efficiency of PGC formation significantly decreased after autophagy inhibition. Our results showed, for the first time, that autophagy plays an indispensable role in the formation of chicken PGCs, which lays the foundation for studying the mechanism of autophagy in chicken PGCs and in bird gene editing and the rescue of endangered birds.